2020
DOI: 10.1080/13625187.2020.1743828
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen-free oral contraception with a 4 mg drospirenone-only pill: new data and a review of the literature

Abstract: Purpose: The contraceptive pill is an effective and safe method of preventing pregnancy. The progestins used for contraception either are components of a combined hormonal contraceptive (tablets, patches or vaginal rings) or are used alone in progestin-only formulations. Progestin-only contraceptives are available as daily oral preparations, subcutaneous or intramuscular injectables (every 1-3 months), subdermal implants (every 3-5 years) and intrauterine systems (every 3-5 years). Long-acting progestins are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…E4/DRSP provides contraceptive efficacy based on PI (0.47 pregnancies/100 woman‐years; 95% CI 0.15–1.11), which is similar to marketed DRSP‐containing COCs, such as Yaz ® (PI = 0.80 pregnancies/100 woman‐years; upper limit 95% CI 1.30) and Yasmin ® (PI = 0.57 pregnancies/100 woman‐years; upper limit 95% CI 0.90). Moreover, E4/DRSP has a lower PI compared with recent studies performed in Europe with a DRSP‐only 4 mg 24/4 contraceptive (Slynd ® , Slinda ® , pooled PI = 0.73 pregnancies/100 woman‐years; 95% CI 0.31–1.43) 27 . E4/DRSP bleeding pattern is comparable to EE‐containing COCs and better than a DRSP‐only 4 mg 24/4 contraceptive 27 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…E4/DRSP provides contraceptive efficacy based on PI (0.47 pregnancies/100 woman‐years; 95% CI 0.15–1.11), which is similar to marketed DRSP‐containing COCs, such as Yaz ® (PI = 0.80 pregnancies/100 woman‐years; upper limit 95% CI 1.30) and Yasmin ® (PI = 0.57 pregnancies/100 woman‐years; upper limit 95% CI 0.90). Moreover, E4/DRSP has a lower PI compared with recent studies performed in Europe with a DRSP‐only 4 mg 24/4 contraceptive (Slynd ® , Slinda ® , pooled PI = 0.73 pregnancies/100 woman‐years; 95% CI 0.31–1.43) 27 . E4/DRSP bleeding pattern is comparable to EE‐containing COCs and better than a DRSP‐only 4 mg 24/4 contraceptive 27 .…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, E4/DRSP has a lower PI compared with recent studies performed in Europe with a DRSP‐only 4 mg 24/4 contraceptive (Slynd ® , Slinda ® , pooled PI = 0.73 pregnancies/100 woman‐years; 95% CI 0.31–1.43). 27 E4/DRSP bleeding pattern is comparable to EE‐containing COCs and better than a DRSP‐only 4 mg 24/4 contraceptive. 27 The adverse event profile was consistent with the use of other COCs, with the most common adverse events being menstrual irregularities, acne and headache.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Both effects were considered clinically not relevant. There is an ongoing debate about the effect of hormonal contraceptives on bone health, and up to date, no closing statement available [51,52]. For 4 mg DRSP, it was demonstrated that the serum oestrogen levels of adult users are in the range of the levels measured during the follicular phase of the normal menstrual cycle.…”
Section: Findings and Interpretationmentioning
confidence: 99%
“…The formulation also offers a longer window for safe dosing. With a half‐life of 30 to 34 hours, it can be taken up to 12 hours late, or 36 hours after the last pill 3 . Norethindrone‐based POPs have a much smaller half‐life, about 10 hours, which results in a roughly 3‐hour window for daily dosing to maintain a steady stream of progestin 4…”
Section: A New Progestin‐only Contraceptive Pill Offers Some Improvemmentioning
confidence: 99%